Synthesis and Bioactivity Evaluation of 2-Arylbenzimidazole Analogues - Zhang, Xu; Huang, Jie; Hu, Fei; Yu, Peng; Hua, Erbing (Asian Journal of Chemistry, 2014)
Benzimidazole is an important drug intermediate. Benzimidazole analogues have shown antibacterial, antiviral, resisting parasites medicinal activity. In this paper, we used phenylenediamine as a starting material through cyclization, acylation reaction to synthetize 2-arybenzimidazole analogues. Twenty-two analogues were synthesized and characterized on the basis of 1H NMR spectra. All this compounds were tested through novel yeast-based screening method to evaluate their bioactivities.